Selection of some native microalgal strains for possibility of bio - oil production in Thailand - Krongkan Janta (2018)
The increasing demand for oil by the world's population has resulted in higher global petroleum prices. Many countries have been trying to explore new energy sources. One such example of this would be biodiesel, which is a form of alternative energy derived from animal and plant lipids. Algae, especially microalgae are organisms, which accumulate high fatty acid in their cells. This research was aimed at comparing the growth rate and high lipid content of native microalgal strains (Chlorella sp. AARL G008, Scenedesmus sp. AARL G022, Monoraphidium sp. AARL G044, Carteria sp. AARL G045 and Carteria sp. AARL G046) with foreign strain (Nannochloropsis limnetica SAG 18.99). All cultures of microalgae were cultivated under Thai climate conditions in Jaworski's Medium (JM). It was found that the native strains grew better than the foreign strain. Scenedesmus sp. AARL G022, Monoraphidium sp. AARL G044 and Carteria sp. AARL G045 were found to be the top three strains in terms of growth rate and lipid content. Carteria sp. AARL G045, the best promising strain, was selected and cultivated in 2 media: JM and Algal Media (AM). Carteria sp. AARL G045 could grow in AM as well as in JM and accumulated similar amounts of total lipids (29.59 mg.L -1 and 27.18 mg.L -1 , respectively). However, AM is ten percent less expensive than JM.